Interior design : - Cerver, Francisco Asensio (Rotovision SA, 1997)
Although they are spaces with clearly differentiated activites, kitchens and bathrooms have common characteristics which distinguish them from other rooms in the house: the presence of water and of task-specific machines and furnishing for cooking and washing. For this reason, the choice and treatment of materials is almost always different from the rest of the house, as they must be resistant to water and damp.